Discretion, Productivity, and Work Satisfaction - Björn Bartling; Ernst Fehr; Klaus M. Schmidt (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2012)
In Bartling, Fehr and Schmidt (2012) we show theoretically and experimentally that it is optimal to grant discretion to workers if (i) discretion increases productivity, (ii) workers can be screened by past performance, (iii) some workers reciprocate high wages with high effort and (iv) employers pay high wages leaving rents to their workers. In this paper we show experimentally that the productivity increase due to discretion is not only sufficient but also necessary for the optimality of granting discretion to workers. Furthermore, we report representative survey evidence on the impact of discretion on workers' welfare, confirming that workers earn rents.
urn:nbn:de:bvb:19-epub-14193-1
Keywords: M5; J3; 330; Kooperative Führung; Arbeitsproduktivität; Arbeitszufriedenheit